2016
DOI: 10.1111/hel.12337
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori and non‐malignant upper gastrointestinal diseases

Abstract: Peptic ulcer disease (PUD) has been further decreased over the last decades along with decreasing prevalence of Helicobacter pylori-associated PUD. A delayed H. pylori eradication has been associated with an increased risk of rehospitalization for complicated recurrent peptic ulcer and reemphasized the importance of eradication especially in patients with peptic ulcer bleeding (PUB). PUB associated with NSAID/aspirin intake and H. pylori revealed an additive interaction in gastric pathophysiology which favors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(4 citation statements)
references
References 27 publications
(42 reference statements)
0
3
0
1
Order By: Relevance
“…The studies that sought to evaluate the association between HP, BE, and ADE found a high variability in the methods, selection bias, and characterization of the study population (199,200) . A meta-analysis reported that the relative risk of BE in patients with HP infection was 0.46 (0.35-0.60); i.e., there was a strong negative association between HP and BE (201) .…”
Section: Level Of Evidence: 3amentioning
confidence: 99%
“…The studies that sought to evaluate the association between HP, BE, and ADE found a high variability in the methods, selection bias, and characterization of the study population (199,200) . A meta-analysis reported that the relative risk of BE in patients with HP infection was 0.46 (0.35-0.60); i.e., there was a strong negative association between HP and BE (201) .…”
Section: Level Of Evidence: 3amentioning
confidence: 99%
“…Os principais processos neoplásicos envolvem o adenorcarcinoma e o linfoma MALT (Mucosa Associated Lymphoid Tissue), formas histológicas mais frequentes encontradas na parede gástrica 4,9,10 .…”
Section: Doenças Relacionadas à Infecção Pelo Helicobacter Pyloriunclassified
“…Upper gastrointestinal dyspepsia symptoms originated from H. pylori infection has been classified as non-functional organic disorders [8] to differentiate it from functional dyspepsia which shows symptom persistence or recurrence after eradication [9]. Symptoms of upper gastrointestinal disorder that occur commonly include intermittent or persistent pain or discomfort in the upper abdomen or lower part of the chest, heartburn, nausea, and a feeling of postprandial fullness, whereas less common symptoms include vomiting, diarrhea, belching, and headache [10][11][12].…”
Section: Introductionmentioning
confidence: 99%